O fenômeno do suicídio na adolescência e as perspectivas de prevenção e aporte do aconselhamento pastoral - Lima, Rosa Marlene Xavier de (2021)
This work emerges from a look directed at adolescence, given the illness that has affected a portion of this population, which, in the midst of the process of physical and emotional development, is swept away by the growing demand for suicide. Suicide is multifactorial and challenges human understanding given its uniqueness and taboo that surrounds it. It is a worldwide phenomenon, which does not select any kind of people, whether of color, ethnicity, social class or age group. Based on a literature review, this research intends to contribute to the prevention of suicide in adolescence. For a better understanding of the subject, we dialogued with some areas of knowledge in order to combine knowledge. The research was organized as follows: first, a conceptual approach to adolescence and questions that possibly trigger processes that cause suffering and pain as vulnerabilities, among others. Next, we enter the universe of the phenomenon of suicide, from medieval roots to our days, the taboo, death, its displacement, the possibility of correlating the incidence of some disorders to suicide and the predisposing factors. And in the third point, we will investigate the approximations between the benefits of care, spirituality and pastoral counseling as a suicide prevention strategy in the promotion of health and well-being and as enhancers in the resignification of life. We believe that to rescue this individual and bring him back to a sphere of balance, well-being and health in his entirety, reconnection with himself and with spirituality is imperative. Thus, it is envisioned that these elucubrations become contributions, as enhancers on the path of resignification of life in adolescence with the support of protective factors such as family, friends, peers and as support networks of institutions and communities, as well as alternative therapies and treatments in place that alleviate their existential suffering and become an effective contribution to the prevention of suicide in adolescence.(AU)